Penggunaan Teknologi Digital dalam Pembelajaran IPA: Study Literature Review - Irnin Agustina Dwi Astuti; Ivan Hanafi; Teguh Trianung Djoko Susanto; Kunto Imbar Nursetyo (UNIVERSITAS INDRAPRASTA PGRI, 2023)
Science learning involves several abstract and complex concepts. To explain these abstract and complex concepts, learning strategies and supporting instructional media are needed. The presence of digital technology has become one alternative in science learning. The use of digital technology in science learning provides valuable opportunities to enhance the quality of learning, expand accessibility, and enrich students' experiences in understanding natural sciences. This study is a literature review of 200 research articles in the Google Scholar database from 2019 to 2022. The research findings show that the most commonly used digital technology in science learning is instructional videos. Digital technology enables easier access to various learning resources, such as videos, simulations, interactive software, and online resources. Students can easily access learning materials with the assistance of technology.